2015
DOI: 10.1007/s00706-015-1508-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of some amino- and sulfanyl-3H-quinazolin-4-one derivatives as potential anticancer agents

Abstract: A series of 6-substituted quinazolinone derivatives were prepared by the reaction of 6-bromoquinazolinones with aryl or alkyl amines and thiols, in the presence of a Pd(OAc) 2 /Xantphos system, under Buchwald-Hartwig-type reaction conditions. The 6-bromoquinazolinones were obtained in the three-components reaction of 5-bromoisatoic anhydride, triethyl orthoformate and an appropriate amine. Biological screening of the potential cytotoxicity of synthesized compounds on HT29 and HCT116 cell lines, as well as on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Our synthetic method simplifies isatin transformations considerably compared to prior methods. Synthesis of isatoic anhydride from isatin previously required using reagents such as peroxides 21,22 , phenyliodide 23 , and NBS 24 ; making benzamide derivatives from isatin required using chromic acid 25 , peroxide/phosphate buffer systems 26 , or in situ generated hydrazoic acid 27,14 ; and generating amino benzamide derivatives from isatoic anhydride required using ammonia 22,28 and ammonium carbonate 29 . In contrast, we can now approach multiple classes of derivatives from IAA using mild, established reactions.…”
Section: Mechanism Of Iaa Formationmentioning
confidence: 99%
“…Our synthetic method simplifies isatin transformations considerably compared to prior methods. Synthesis of isatoic anhydride from isatin previously required using reagents such as peroxides 21,22 , phenyliodide 23 , and NBS 24 ; making benzamide derivatives from isatin required using chromic acid 25 , peroxide/phosphate buffer systems 26 , or in situ generated hydrazoic acid 27,14 ; and generating amino benzamide derivatives from isatoic anhydride required using ammonia 22,28 and ammonium carbonate 29 . In contrast, we can now approach multiple classes of derivatives from IAA using mild, established reactions.…”
Section: Mechanism Of Iaa Formationmentioning
confidence: 99%
“…To optimize the reaction conditions, we investigated the reaction of 4-bromo-2-methylphthalazin-1(2 H )-one ( 3a ) with morpholine as the model substrates. Previously, we have observed that the coupling system involving Xantphos/Pd(OAc) 2 (used in the ratio of 15 mol %/15 mol % or 30 mol %/30 mol %) and t- BuOK or DIPEA in 1,4-dioxane as the solvent was effective for the C–N or C–S bond formation [ 30 31 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have demonstrated a strategy for the synthesis of phthalazinone and phthalazine derivatives of type 4 containing an alkylsulfanyl functional group at the 4 position, that is based on the Pd-catalyzed coupling reaction between mercaptanes and 4-bromolactams ( Scheme 1 , route A) [ 30 ]. In continuing our efforts on the functionalization of phthalazinones and quinazolinones [ 30 31 ] and taking into consideration the biological importance of aminophthalazine derivatives, we decided to apply the methodology based on the palladium-catalyzed C–N-bond formation (Buchwald–Hartwig-type reaction) as a convenient and effective approach for the synthesis of the new phthalazinone derivatives 5 and 6 ( Scheme 1 , route B).…”
Section: Introductionmentioning
confidence: 99%
“…Zayed et al [58] developed a quinazolinone-bearing sulphonamide moiety compound 36 which upon MTT ass showed IC50 value of 2.51 μM, whereas, the reference drug (methotrexate) exhibited an IC50 value of 2.4 μM, against Michigan Cancer Foundation-7 (MCF-7) breast cancer cells, National Cancer Institute (NCI) lung cancer cells and Human Embryonic Kidney-293 (HEK-293) normal kidney cell. 6-Substituted quinazolinone compound 37 was reported by Malinowski et al, revealed significant activity toward both HT29 (IC50 = 50.90 μM) and HCT116 (IC50 = 46.00 μM) cells lines [59].…”
Section: Anticancer Activitymentioning
confidence: 90%